Inhalation Medication Administration in Children with Pneumonia with Ineffective Airway Clearance: Case Study - Kusumaningrum, Nintya Vela; Arini, Tri; Ambarwati, Ambarwati; Harigustian, Yayang (GLOBAL HEALTH SCIENCE GROUP, 2023)
Pneumonia is responsible for the deaths of 740,180 infants and is the leading cause of mortality among this age group. In Indonesia, pneumonia accounts for 16% of all deaths and often leads to ineffective airway clearance, necessitating appropriate treatment such as inhalation medication to reduce sputum viscosity or widen the airways. To determine the effectiveness of inhalation medication administration in children with pneumonia experiencing ineffective airway clearance in the West Padmanaba Ward of Dr. Sardjito Yogyakarta General Hospital. The methodology employed in this case study aims to describe and explore the administration of inhalation medication to pediatric pneumonia patients with ineffective airway clearance for 3x24 hours at Dr. Sardjito Yogyakarta General Hospital. After administering inhalation medication for 3x8 hours to children with pneumonia experiencing ineffective airway clearance, partial resolution of the problem was observed. Inhalation medication administration was effective for pediatric pneumonia patients with ineffective airway clearance, exemplified in the case of An.M.